Pollen morphology of some species of the Family Asteraceae from the Alpine Zone, Deosai Plateau, northern Pakistan - Mushtaq Ahmad; Abida Bano; Muhammad Zafar; Mir Ajab Khan; Muhammad Jamshed Iqbal Chaudhry; Shazia Sultana (Palynology, 2013)

Removal of Phenol Using Sulphate Radicals Activated by Natural Zeolite-Supported Cobalt Catalysts - Syaifullah Muhammad; Edy Saputra; Hongqi Sun; H. M. Ang; Moses O. Tadé; Shaobin Wang (Water, Air, & Soil Pollution, 2013)

Risk-based flood zoning employing expected annual damages: the Chenab River case study - Muhammad Atiq Ur Rehman Tariq (Stochastic Environmental Research and Risk Assessment, 2013)

Involvement of Ca2+ and CaM3 in Regulation of Thermotolerance in Lily (Lilium longiflorum) - Xing Cao; Jin Yi; Ze Wu; Xian Luo; Xionghui Zhong; Jian Wu; Muhammad Ali Khan; Yang Zhao; Mingfang Yi (Plant Molecular Biology Reporter, 2013)

Molecular Characterization of Chenopodium album Chloroplast Small Heat Shock Protein and Its Expression in Response to Different Abiotic Stresses - Noor Ul Haq; Muhammad Ammar; Asghari Bano; Dawn S. Luthe; Scott A. Heckathorn; Samina N. Shakeel (Plant Molecular Biology Reporter, 2013)

Combination of sulfamethoxazole and selenium in anticancer therapy: a novel approach - Ritu Gupta; Imran Kazmi; Muhammad Afzal; Ruqaiyah Khan; Mohit Chauhan; Fahad A. Al-Abbasi; Aftab Ahmad; Firoz Anwar (Molecular and Cellular Biochemistry, 2013)

2,5-Disubstituted-1,3,4-oxadiazoles: thymidine phosphorylase inhibitors - Khalid Mohammed Khan; Mubeen Rani; Nida Ambreen; Muhammad Ali; Sajjad Hussain; Shahnaz Perveen; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Synthesis and biological evaluation of some N 4-aryl-substituted 5-fluoroisatin-3-thiosemicarbazones - Humayun Pervez; Naveeda Saira; Mohammad Saeed Iqbal; Muhammad Yaqub; Khalid Mohammed Khan (Medicinal Chemistry Research, 2013)

Molecular insights to explore abietane diterpenes as new LOX inhibitors - Inamullah Khan; Muhammad Nisar; Armando Zarrelli; Giovanni Di Fabio; Farah Gul; Syed Naeemuddin Gilani; Muhammad Raza Shah; Amir Zada Khan; Samiullah; Hazrat Amin (Medicinal Chemistry Research, 2013)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Anticancer effect of ursolic acid stearoyl glucoside in chemically induced hepatocellular carcinoma - Imran Kazmi; Anil Raj Narooka; Muhammad Afzal; Rajbala Singh; Fahad A. Al-Abbasi; Aftab Ahmad; Firoz Anwar (Journal of Physiology and Biochemistry, 2013)

Effect of diclofenac and antidepressants on the inflammatory response in astrocyte cell culture - Md. Mamun Al-Amin; Mir Muhammad Nasir Uddin; Md. Mahbubur Rahman; Hasan Mahmud Reza; Md. Sohel Rana (Inflammopharmacology, 2013)

Interactive effect of cobalt and nitrogen on growth, nodulation, yield and protein content of field grown pea - Fahmida Mir Akbar; Mohsin Zafar; Abdul Hamid; Maqsood Ahmed; Abdul Khaliq; Muhammad Riaz Khan; Zahid ur Rehman (Horticulture, Environment, and Biotechnology, 2013)

Occurrence of potato mop-top virus in Northwest of Pakistan - Muhammad Arif; Murad Ali; Anayatur Rehman; Muhammad Fahim (European Journal of Plant Pathology, 2013)

Energy, environment and growth nexus in South Asia - Muhammad Zeshan; Vaqar Ahmed (Environment, Development and Sustainability, 2013)

Synthesis of chemically cross-linked polyvinyl alcohol-co-poly (methacrylic acid) hydrogels by copolymerization; a potential graft-polymeric carrier for oral delivery of 5-fluorouracil - Muhammad Usman Minhas; Mahmood Ahmad; Liaqat Ali; Muhammad Sohail (DARU Journal of Pharmaceutical Sciences, 2013)
Background of the Study The propose of the present work was to develop chemically cross-linked polyvinyl alcohol-co-poly(methacrylic acid) hydrogel (PVA-MAA hydrogel) for pH responsive delivery of 5-Fluorouracil (5-FU). Methods PVA based hydrogels were prepared by free radical copolymerization. PVA has been cross-linked chemically with monomer (methacrylic acid) in aqueous medium, cross-linking agent was ethylene glycol di-methacrylate (EGDMA) and benzoyl peroxide was added as reaction initiator. 5-FU was loaded as model drug. FTIR, XRD, TGA and DSC were performed for characterization of copolymer. Surface morphology was studied by SEM. pH sensitive properties were evaluated by swelling dynamics and equilibrium swelling ratio at low and higher pH. Results FTIR, XRD, TGA and DSC studies confirmed the formation of new copolymer. Formulations with higher MAA contents showed maximum swelling at 7.4 pH. High drug loading and higher drug release has been observed at pH 7.4. Conclusions The current study concludes that a stable copolymeric network of PVA was developed with MAA. The prepared hydrogels were highly pH responsive. This polymeric network could be a potential delivery system for colon targeting of 5-FU in colorectal cancers.

The release behavior and kinetic evaluation of tramadol HCl from chemically cross linked Ter polymeric hydrogels - Muhammad A Malana; Rubab Zohra (DARU Journal of Pharmaceutical Sciences, 2013)

Genetic diversity and population structure of Moringa oleifera - Umbreen Shahzad; M. Awais Khan; Muhammad Jaffar Jaskani; Iqrar Ahmad Khan; Schuyler S. Korban (Conservation Genetics, 2013)

Definitions and engineering classifications of tropical lowland peats - Mohamad Tarmizi Mohamad Zulkifley; Tham Fatt Ng; John Kuna Raj; Roslan Hashim; Azman Ghani; Mustaffa Kamal Shuib; Muhammad Aqeel Ashraf (Bulletin of Engineering Geology and the Environment, 2013)

Preservation of Bone Structure and Function by Lithothamnion sp. Derived Minerals - Muhammad Nadeem Aslam; Ingrid Bergin; Karl Jepsen; Jaclynn M. Kreider; Kristin H. Graf; Madhav Naik; Steven A. Goldstein; James Varani (Biological Trace Element Research, 2013)

Identification of Oviposition Attractants of the Secondary Screwworm, Cochliomyia macellaria (F.) Released from Rotten Chicken Liver - Junwei J. Zhu; Muhammad F. Chaudhury; Khanobporn Tangtrakulwanich; Steven R. Skoda (Journal of Chemical Ecology, 2013)

A novel dsRNA element isolated from the Aspergillus foetidus mycovirus complex - Zisis Kozlakidis; Noemi Herrero; Selin Ozkan; Muhammad F. Bhatti; Robert H. A. Coutts (Archives of Virology, 2013)

Quantitative trait loci (QTL) associated with growth rate trait in common carp (Cyprinus carpio) - Muhammad Younis Laghari; Yan Zhang; Punhal Lashari; Xiaofeng Zhang; Peng Xu; Baoping Xin; Xiaowen Sun (Aquaculture International, 2013)

Ion-Pair Chromatography for Simultaneous Analysis of Ethionamide and Pyrazinamide from Their Porous Microparticles - Chintan J. Bhanushali; Ahmed S. Zidan; Ziyaur Rahman; Muhammad J. Habib (AAPS PharmSciTech, 2013)

Tree species as a potential source of bio-herbicides for controlling Parthenium hysterophorus L. - Muhammad Ehsan Safdar; Asif Tanveer; Abdul Khaliq; Muhammad Shahbaz Naeem; Salman Ahmad (Natural Product Research, 2013)

New acylated oligosaccharides from Pistacia integerrima - Zia Ullah; Rashad Mehmood; Muhammad Imran; Abdul Malik; Rehana A. Afzal (Natural Product Research, 2013)

Fungal endophyte Penicillium janthinellum LK5 improves growth of ABA-deficient tomato under salinity - Abdul Latif Khan; Muhammad Waqas; Abdur Rahim Khan; Javid Hussain; Sang-Mo Kang; Syed Abdullah Gilani; Muhammad Hamayun; Jae-Ho Shin; Muhammad Kamran; Ahmed Al-Harrasi; Byung-Wook Yun; Muhammad Adnan; et al. (World Journal of Microbiology and Biotechnology, 2013)

Risks factors associated with subclinical mastitis in water buffaloes in Pakistan - Riaz Hussain; Muhammad Tariq Javed; Ahrar Khan; Ghulam Muhammad (Tropical Animal Health and Production, 2013)

Functional evolution of cis-regulatory modules of STMADS11 superclade MADS-box genes - Muhammad Ramzan Khan; Ghulam Muhammad Ali (Plant Molecular Biology, 2013)

IL-1Ra and its Delivery Strategies: Inserting the Association in Perspective - Muhammad Sajid Hamid Akash; Kanwal Rehman; Shuqing Chen (Pharmaceutical Research, 2013)

Molecular classification of Pakistani collared dove through DNA barcoding - Ali Raza Awan; Emma Umar; Muhammad Zia ul Haq; Sehrish Firyal (Molecular Biology Reports, 2013)

Lepiota vellingana sp. nov. (Basidiomycota, Agaricales) a new species from Lahore, Pakistan - Rizwana Nawaz; A. N. Khalid; Muhammad Hanif; A. Razaq (Mycological Progress, 2013)

Expressions of Tumor Necrosis Factor Alpha and MicroRNA-155 in Immature Rat Model of Status Epilepticus and Children with Mesial Temporal Lobe Epilepsy - Muhammad Usman Ashhab; Ahmed Omran; Huimin Kong; Na Gan; Fang He; Jing Peng; Fei Yin (Journal of Molecular Neuroscience, 2013)

Characterization of a novel missense mutation in the prodomain of GDF5, which underlies brachydactyly type C and mild Grebe type chondrodysplasia in a large Pakistani family - Muhammad Farooq; Hiroyuki Nakai; Atsushi Fujimoto; Hiroki Fujikawa; Klaus Wilbrandt Kjaer; Shahid Mahmood Baig; Yutaka Shimomura (Human Genetics, 2013)

Trace metals in Ganges soft-shell turtle (Aspideretes gangeticus) from two barrage: Baloki and Rasul, Pakistan - Riffat Naseem Malik; Bushra Ghaffar; Muhammad Zaffar Hashmi (Environmental Science and Pollution Research, 2013)

Root Colonization and Phytostimulation by Phytohormones Producing Entophytic Nostoc sp. AH-12 - Anwar Hussain; Muhammad Hamayun; Syed Tariq Shah (Current Microbiology, 2013)

Description of Goussia kuehae n. sp. (Apicomplexa: Eimeriidae) infecting the Asian seabass, Lates calcarifer (Bloch) (Perciformes: Latidae), cultured in Malaysian fish farms - Csaba Székely; Muhammad Hafiz Borkhanuddin; Faizah Shaharom; Mohd Shukri Adam Embong; Kálmán Molnár (Systematic Parasitology, 2013)

Organelle antioxidants improve microspore embryogenesis in wheat and triticale - Muhammad Asif; François Eudes; Aakash Goyal; Eric Amundsen; Harpinder Randhawa; Dean Spaner (In Vitro Cellular & Developmental Biology - Plant, 2013)

Tephrochronology of the Toba tuffs: four primary glass populations define the 75‐ka Youngest Toba Tuff, northern Sumatra, Indonesia - J. A. WESTGATE; N. J. G. PEARCE; W. T. PERKINS; S. J. PREECE; C. A. CHESNER; R. F. MUHAMMAD (Journal of Quaternary Science, 2013)
Four primary glass populations, well defined by their Sr, Ba and Y concentrations, occur in the Youngest Toba Tuff (YTT), which was deposited during a supereruption of the Toba caldera complex in northern Sumatra 75 ka. Average concentrations of major and trace elements indicate a coherent, systematic variation of glass composition across populations. No clear pattern in the areal distribution of these four glass groups can be discerned. The multiple glass populations of the YTT easily distinguish it from the single homogeneous glass population of the Middle Toba Tuff (∼500 ka), as represented by its basal vitrophyre, and that of the Oldest Toba Tuff (∼800 ka), as represented by ash Layer D at the Ocean Drilling Program site 758 in the Indian Ocean.

Loasins A and B, new flavonoids from Eremostachys loasifolia - Uzma Rasheed Mughal; Ghulam Fareed; Arif Zubair; Abdul Malik; Muhammad Ali Versiani; Nighat Afza; Rasool Bakhsh Tareen (Natural Product Research, 2013)

Responses of energy balance, physiology, and production for transition dairy cows fed with a low-energy prepartum diet during hot season - Huawei Su; Yachun Wang; Qian Zhang; Fuwei Wang; Zhijun Cao; Muhammad Aziz Ur Rahman; Binghai Cao; Shengli Li (Tropical Animal Health and Production, 2013)

Maize seedling phosphorus nutrition: Allocation of remobilized seed phosphorus reserves and external phosphorus uptake to seedling roots and shoots during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Muhammad Shahid; Muhammad Aslam; Muhammad Zia-ur-Rehman; Muhammad Ashfaq Wahid; Sylvain Pellerin (Plant and Soil, 2013)

Cefotaxime prevents microbial contamination and improves microspore embryogenesis in wheat and triticale - Muhammad Asif; François Eudes; Harpinder Randhawa; Eric Amundsen; Jay Yanke; Dean Spaner (Plant Cell Reports, 2013)

Distinctive microRNA expression signatures in proton-irradiated mice - Shahid Yar Khan; Muhammad Akram Tariq; James Patrick Perrott; Christopher Drew Brumbaugh; Hyunsung John Kim; Muhammad Imran Shabbir; Govindarajan T. Ramesh; Nader Pourmand (Molecular and Cellular Biochemistry, 2013)

Synthesis of metal(II) [M = Cu, Mn, Zn] Schiff base complexes and their Pro-apoptotic activity in liver tumor cells via caspase activation - Abeer Mohamed Farag; Teoh Siang Guan; Hasnah Osman; A. M. S. Abdul Majid; Muhammad Adnan Iqbal; Mohamed B. Khadeer Ahamed (Medicinal Chemistry Research, 2013)

Synthesis, structure, anticancer, and antioxidant activity of para-xylyl linked bis-benzimidazolium salts and respective dinuclear Ag(I) N-heterocyclic carbene complexes (Part-II) - Rosenani A. Haque; Muhammad Adnan Iqbal; Patrick Asekunowo; A. M. S. Abdul Majid; Mohamed B. Khadeer Ahamed; Muhammad Ihtisham Umar; Sawsan S. Al-Rawi; Fouad Saleih R. Al-Suede (Medicinal Chemistry Research, 2013)

Initiation of a convective dust storm over North India on 21 April 2010 inferred using satellite data - Nirmala Devidas Desouza; Rajnish Kurchania; Muhammad Shums Qureshi (Meteorology and Atmospheric Physics, 2013)

A genetical genomics approach reveals new candidates and confirms known candidate genes for drip loss in a porcine resource population - Hanna Heidt; Mehmet Ulas Cinar; Muhammad Jasim Uddin; Christian Looft; Heinz Jüngst; Dawit Tesfaye; Astrid Becker; Andreas Zimmer; Siriluck Ponsuksili; Klaus Wimmers; Ernst Tholen; Karl Schellander; et al. (Mammalian Genome, 2013)

Increased fitness and realized heritability in emamectin benzoate-resistant Chrysoperla carnea (Neuroptera: Chrysopidae) - Muhammad Mudassir Mansoor; Naeem Abbas; Sarfraz Ali Shad; Attaullah Khan Pathan; Muhammad Razaq (Ecotoxicology, 2013)

Modulation of Reproductive Behaviors by Non-Host Volatiles in the Polyphagous Egyptian Cotton Leafworm, Spodoptera littoralis - Muhammad Binyameen; Altaf Hussain; Fatemeh Yousefi; Göran Birgersson; Fredrik Schlyter (Journal of Chemical Ecology, 2013)

Forecasting flood risk in the Indus River system using hydrological parameters and its damage assessment - Bushra Khan; Muhammad Jawed Iqbal (Arabian Journal of Geosciences, 2013)

Chemical and physical control processes on the development of caves in the Injana Formation, Central Iraq - Salih Muhammad Awadh; Zenah Saleem Abood; Murtadha Jabar Eisa (Arabian Journal of Geosciences, 2013)

LONG‐TERM GROUNDWATER QUALITY AND SALINE INTRUSION ASSESSMENT IN AN IRRIGATED ENVIRONMENT: A CASE STUDY OF THE AQUIFER UNDER THE LBDC IRRIGATION SYSTEM - Muhammad Basharat; Ata‐Ur‐Rehman Tariq (Irrigation and Drainage, 2013)
Pakistan's irrigation system is more than a century old. Due to the increasing population and consequent intensifying agriculture, dependence on groundwater is successively increasing. The underground reservoir that was recharged during the first half of the twentieth century by the newly built irrigation system with low cropping intensities is now being overexploited. Groundwater quality is variable, both vertically and horizontally, with the exception of areas adjacent to rivers, where it is fresh. This paper describes groundwater quality in the Lower Bari Doab Canal (LBDC) irrigation system based on 47 years of historic water quality data (TDS, SAR and RSC). Areas are delineated in the form of zones and depths. The tail end of the command is facing severe groundwater depletion, whereas in certain parts, groundwater quality deterioration with the passage of time has also been detected. Possible reasons and mechanisms of saline intrusion within the aquifer are described. Lateral saline intrusion is not a major issue due to very slow groundwater movement. But in areas with saline groundwater lying below the upper layer of irrigation leaked fresh water, mobilization of deeper saline water is taking place as a result of pumping by farmers. In addition, results of the solute transport model and MODPATH runs were evaluated in support of water quality analysis and groundwater flow rates. Copyright © 2013 John Wiley & Sons, Ltd.

Gut Lactobacillus sp. bacteria as probiotics for Portunus pelagicus (Linnaeus, 1758) larviculture: effects on survival, digestive enzyme activities and water quality - Allah Dad Talpur; Abdul Jabbar Memon; Muhammad Iqbal Khan; Mhd Ikhwanuddin; Muhd Danish Daniel Abdullah; Abol-Munafi Ambok Bolong (Invertebrate Reproduction & Development, 2013)

Erratum to: Daily Forecasting of Dam Water Levels: Comparing a Support Vector Machine (SVM) Model With Adaptive Neuro Fuzzy Inference System (ANFIS) - Afiq Hipni; Ahmed El-shafie; Ali Najah; Othman Abdul Karim; Aini Hussain; Muhammad Mukhlisin (Water Resources Management, 2013)

Minireview on Achillea millefolium Linn - Muhammad Akram (The Journal of Membrane Biology, 2013)

Regulation in Plant Stress Tolerance by a Potential Plant Growth Regulator, 5-Aminolevulinic Acid - Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2013)

Impact of Condensates Containing Chloride and Sulphate on the Corrosion in Automotive Exhaust Systems - Reina Hashimoto; Gregor Mori; Muhammad Yasir; Uwe Tröger; Helmut Wieser (BHM Berg- und Hüttenmännische Monatshefte, 2013)

The diversity of Rhizobia, Sinorhizobia and novel non-Rhizobial Paenibacillus nodulating wild herbaceous legumes - Sadia Latif; SamiUllah Khan; Muhammad Naveed; Ghulam Mustafa; Tasmia Bashir; Abdul Samad Mumtaz (Archives of Microbiology, 2013)

Deterministic and probabilistic seismic hazard analysis for Gwadar City, Pakistan - Shafiq Ur Rehman; Muhammad Khalid; Asif Ali; Abd El-aziz Khairy Abd El-Aal (Arabian Journal of Geosciences, 2013)

Salinity and drought interaction in wheat (Triticum aestivum L.) is affected by the genotype and plant growth stage - Muhammad Saqib; Javaid Akhtar; Ghulam Abbas; Muhammad Nasim (Acta Physiologiae Plantarum, 2013)

5-Aminolevulinic acid enhances photosynthetic gas exchange, chlorophyll fluorescence and antioxidant system in oilseed rape under drought stress - Dan Liu; Lingtong Wu; Muhammad Shahbaz Naeem; Hongbo Liu; Xiangqin Deng; Ling Xu; Fan Zhang; Weijun Zhou (Acta Physiologiae Plantarum, 2013)

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications - Iqbal Ahmad; Kiran Qadeer; Kefi Iqbal; Sofia Ahmed; Muhammad Ali Sheraz; Syed Abid Ali; Tania Mirza; Ambreen Hafeez (AAPS PharmSciTech, 2013)

Daily Forecasting of Dam Water Levels: Comparing a Support Vector Machine (SVM) Model With Adaptive Neuro Fuzzy Inference System (ANFIS) - Afiq Hipni; Ahmed El-shafie; Ali Najah; Othman Abdul Karim; Aini Hussain; Muhammad Mukhlisin (Water Resources Management, 2013)

Seroprevalence of bovine tuberculosis infection in yaks (Bos grunniens) on the Qinghai-Tibetan Plateau of China - Zhaoqing Han; Jianfeng Gao; Muhammad Shahzad; Xianrong Meng; Mengyuan Liu; Kerong Zhang; Ding Zhang; Aizhen Guo; Suolang Sizhu; Jiakui Li (Tropical Animal Health and Production, 2013)

Modelling for rearrangement of fusiform initials during radial growth of the vascular cambium in Pinus sylvestris L. - Wiesław Włoch; Anna Wilczek; Joanna Jura-Morawiec; Paweł Kojs; Muhammad Iqbal (Trees, 2013)

Drought-induced adaptive changes in the seedling anatomy of Acacia ehrenbergiana and Acacia tortilis subsp. raddiana - Ibrahim M. Aref; Abdallah I. Ahmed; Pervaiz R. Khan; Hashim A. El-Atta; Muhammad Iqbal (Trees, 2013)

Phosphorus accumulation in grains of japonica rice as affected by nitrogen fertilizer - Junguo Bi; Zhenghui Liu; Zhaomiao Lin; Md A. Alim; Muhammad I. A. Rehmani; Ganghua Li; Qiangsheng Wang; Shaohua Wang; Yanfeng Ding (Plant and Soil, 2013)

Drought alters interactions between root and foliar herbivores - Muhammad Tariq; John T. Rossiter; Denis J. Wright; Joanna T. Staley (Oecologia, 2013)

Synthesis and biological evaluation of new [1,3,4]thiadiazepino[7,6-b]quinolin-2-amines as potent anti-microbial agents - Hasnain Muhammad Raza; Nada-E-Ali Rizvi; Hamid Latif Siddiqui; Arshad Javaid; Mazhar Iqbal (Medicinal Chemistry Research, 2013)

Trypsin inhibitory potential and microbial transformation of rutin isolated from Citrus sinensis - Muhammad Asam Raza; Durre Shahwar (Medicinal Chemistry Research, 2013)

Drug interactions and synthesis of cefpirome with hypoglycemic agents - Muhammad Nawaz; Muhammad Saeed Arayne; Najma Sultana (Medicinal Chemistry Research, 2013)

How disaggregated should information be for a sound food security policy? - Muhammad Khalid Bashir; Steven Schilizzi (Food Security, 2013)

Molecular identification of Trichogramma species from Pakistan, using ITS-2 region of rDNA - Muhammad Farooq Nasir; Gregor Hagedorn; Carmen Büttner; Christoph Reichmuth; Matthias Schöller (BioControl, 2013)

SLC26A4 Mutations in Patients with Moderate to Severe Hearing Loss - Muhammad Riaz Khan; Rasheeda Bashir; Sadaf Naz (Biochemical Genetics, 2013)

Nitrous Oxide Emissions from Yellow Brown Soil as Affected by Incorporation of Crop Residues With Different Carbon-to-Nitrogen Ratios: A Case Study in Central China - Shan Lin; Javed Iqbal; Ronggui Hu; Muhammad Shaaban; Jianbo Cai; Xi Chen (Archives of Environmental Contamination and Toxicology, 2013)

Two new triterpenes from Alstonia scholaris flowers - Nighat Sultana; Zafar Saeed Saify; Muhammad Saleem; Mustafa Kamal (Natural Product Research, 2013)

A new bivariate Gamma distribution generated from functional scale parameter with application to drought data - Muhammad Mohsin; Albrecht Gebhardt; Jürgen Pilz; Gunter Spöck (Stochastic Environmental Research and Risk Assessment, 2013)

Pathological speech signal analysis and classification using empirical mode decomposition - Muhammad Kaleem; Behnaz Ghoraani; Aziz Guergachi; Sridhar Krishnan (Medical & Biological Engineering & Computing, 2013)

17β-Estradiol Impedes Bax-Involved Mitochondrial Apoptosis of Retinal Nerve Cells Induced by Oxidative Damage via the Phosphatidylinositol 3-Kinase/Akt Signal Pathway - Hongbo Li; Baoying Wang; Chunhui Zhu; Yan Feng; Shaolan Wang; Muhammad Shahzad; Chenghu Hu; Mingshu Mo; Fangying Du; Xiaorui Yu (Journal of Molecular Neuroscience, 2013)

Polypharmacy (herbal and synthetic drug combination): a novel approach in the treatment of type-2 diabetes and its complications in rats - Rupinder Kaur; Muhammad Afzal; Imran Kazmi; Iqbal Ahamd; Zubair Ahmed; Babar Ali; Sayeed Ahmad; Firoz Anwar (Journal of Natural Medicines, 2013)

Absorption and Fluorescence Emission Attributes of a Fluorescent dye: 2,3,5,6-Tetracyano-p-Hydroquinone - Muhammad Zahid; Günter Grampp; Asim Mansha; Ijaz Ahmad Bhatti; Sadia Asim (Journal of Fluorescence, 2013)

Cytotoxic, phytotoxic, and mutagenic appraisal to ascertain toxicological potential of particulate matter emitted from automobiles - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Imran Altaf; Aftab Ahmad Anjum (Environmental Science and Pollution Research, 2013)

Study of contaminant transport at an open-tipping waste disposal site - Muhammad Aqeel Ashraf; Ismail Yusoff; Mohamad Yusof; Yatimah Alias (Environmental Science and Pollution Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Rapamycin Induces Apoptosis When Autophagy is Inhibited in T-47D Mammary Cells and Both Processes are Regulated by Phlda1 - Ahmed Ismail Hassan Moad; Tengku Sifzizul Tengku Muhammad; Chern Ein Oon; Mei Lan Tan (Cell Biochemistry and Biophysics, 2013)

The scientific value of the largest remaining old-growth red pine forests in North America - Madhur Anand; Mark Leithead; Lucas C. R. Silva; Christopher Wagner; Muhammad Waseem Ashiq; Jacob Cecile; Igor Drobyshev; Yves Bergeron; Arundhati Das; Cara Bulger (Biodiversity and Conservation, 2013)

A Battery of Bioassays for the Evaluation of Phenanthrene Biotoxicity in Soil - Muhammad Imran Khan; Sardar Alam Cheema; Xianjin Tang; Muhammad Zaffar Hashmi; Chaofeng Shen; Joonhong Park; Yingxu Chen (Archives of Environmental Contamination and Toxicology, 2013)

Hydrochemistry and pollution probability of selected sites along the Euphrates River, Western Iraq - Salih Muhammad Awadh; Rasol Muhamad Ahmed (Arabian Journal of Geosciences, 2013)

A probabilistic approach for estimating return period of extreme annual rainfall in different cities of Punjab - M. J. Iqbal; Muhammad Ali (Arabian Journal of Geosciences, 2013)

Modelling land use change across elevation gradients in district Swat, Pakistan - Muhammad Qasim; Klaus Hubacek; Mette Termansen; Luuk Fleskens (Regional Environmental Change, 2013)

Model-Based Evaluation of Maturity Type of Potato Using a Diverse Set of Standard Cultivars and a Segregating Diploid Population - Muhammad Sohail Khan; Herman J. van Eck; Paul C. Struik (Potato Research, 2013)

Metabolomics for the rapid dereplication of bioactive compounds from natural sources - Nancy Dewi Yuliana; Muhammad Jahangir; Robert Verpoorte; Young Hae Choi (Phytochemistry Reviews, 2013)

Why was the 2008 Indian Ocean Dipole a short-lived event? - Iskhaq Iskandar; Muhammad Irfan; Fadli Saymsuddin (Ocean Science Journal, 2013)

Probabilistic seismic hazard analysis and spectral accelerations for United Arab Emirates - Zahid Khan; Magdi El-Emam; Muhammad Irfan; Jamal Abdalla (Natural Hazards, 2013)

Hepatoprotective potential of new steroid against carbon tetrachloride-induced hepatic injury - Muhammad Afzal; Ruqaiyah Khan; Imran Kazmi; Firoz Anwar (Molecular and Cellular Biochemistry, 2013)

The potential feasibility for soil improvement, based on the properties of biochars pyrolyzed from different feedstocks - Zhongmin Dai; Jun Meng; Niaz Muhammad; Xingmei Liu; Haizhen Wang; Yan He; Philip C. Brookes; Jianming Xu (Journal of Soils and Sediments, 2013)

Expression Patterns of miR-124, miR-134, miR-132, and miR-21 in an Immature Rat Model and Children with Mesial Temporal Lobe Epilepsy - Jing Peng; Ahmed Omran; Muhammad Usman Ashhab; Huimin Kong; Na Gan; Fang He; Fei Yin (Journal of Molecular Neuroscience, 2013)

Arsenic Toxicity on Ludwigia octovalvis in Spiked Sand - Harmin Sulistiyaning Titah; Siti Rozaimah Sheikh Abdullah; Idris Mushrifah; Nurina Anuar; Hassan Basri; Muhammad Mukhlisin (Bulletin of Environmental Contamination and Toxicology, 2013)

Molecular characterization of a new synthetic cry2ab gene in Nicotiana tabacum - Sohail Mehmood Karimi; Muhammad Nouman Sohail; Imran Amin; Shahid Mansoor; Zahid Mukhtar (Biotechnology Letters, 2013)

Systematic validation of candidate reference genes for qRT-PCR normalization under iron deficiency in Arabidopsis - Bin Han; Zheng Yang; Muhammad Kaleem Samma; Ren Wang; Wenbiao Shen (BioMetals, 2013)

Dominant impact of South Asian low heat on summer monsoon rainfall over Central India - Muhammad Jawed Iqbal; Mirza Jawwad Baig; Saba Naz (Arabian Journal of Geosciences, 2013)

The zinc finger protein ZAT11 modulates paraquat-induced programmed cell death in Arabidopsis thaliana - Muhammad Kamran Qureshi; Neerakkal Sujeeth; Tsanko S. Gechev; Jacques Hille (Acta Physiologiae Plantarum, 2013)

Studies on Tolfenamic Acid–Chitosan Intermolecular Interactions: Effect of pH, Polymer Concentration and Molecular Weight - Sofia Ahmed; Muhammad Ali Sheraz; Ihtesham Ur Rehman (AAPS PharmSciTech, 2013)

Participatory Optimization Scenario for Water Resources Management: A Case from Jordan - Maisa’a W. Shammout; Muhammad Shatanawi; Sawsan Naber (Water Resources Management, 2013)

Synthesis and anticancer activity of para-xylyl linked bis-benzimidazolium salts and respective Ag(I) N-heterocyclic carbene complexes - Muhammad Adnan Iqbal; Rosenani A. Haque; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid; Sawsan S. Al-Rawi (Medicinal Chemistry Research, 2013)

Isolation of long-chain esters from the rhizome of Polygonatum verticillatum by potent tyrosinase inhibition - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Izhar-ul-Haq; Naveed Muhammad; Rukhsana Ghaffar (Medicinal Chemistry Research, 2013)

Eggs Distribution Behaviour of Dubas Bug (Ommatissus Lybicus: Homoptera: Tropiduchidae) in Relation to Seasons and Some Physico- Morphic Characters of Date Palm Leaves - Arif Shah; Ata Ul Mohsin; Zahid Hafeez; Muhammad Naeem; Muhammad Irfan Ul Haq (Journal of Insect Behavior, 2013)

Novel Fluorescent Membrane for Metronidazole Sensing Prepared by Covalent Immobilization of a Pyrenebutyric Acid Derivative - Asigul Muhammad; Turghun Muhammad; Osmanjan Yimit; Burabiye Yakup (Journal of Fluorescence, 2013)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Monitoring the drastic growth of ship breaking yards in Sitakunda: a threat to the coastal environment of Bangladesh - Hasan Muhammad Abdullah; M. Golam Mahboob; Mehmuna R. Banu; Dursun Zafer Seker (Environmental Monitoring and Assessment, 2013)

Oil spill cleanup using graphene - Muhammad Z. Iqbal; Ahmed A. Abdala (Environmental Science and Pollution Research, 2013)

Organic amendments differ in their effect on microbial biomass and activity and on P pools in alkaline soils - Muhammad Asghar Malik; Khalid Saifullah Khan; Petra Marschner; Safdar Ali (Biology and Fertility of Soils, 2013)

Development of a Polygonum minus cell suspension culture system and analysis of secondary metabolites enhanced by elicitation - Muhammad Faizan A. Shukor; Ismanizan Ismail; Zamri Zainal; Normah Mohd Noor (Acta Physiologiae Plantarum, 2013)

Chemical composition of essential oil from Calligonum polygonoides Linn. - Muhammad Qasim Samejo; Shahabuddin Memon; Muhammad Iqbal Bhanger; Khalid Mohammed Khan (Natural Product Research, 2013)

Prospects of raising Sahiwal cow calves for veal production under tropical environment - Shaukat Ali Bhatti; Kamran Nazir; Muhammad Jamil Basra; Muhammad Sajjad Khan; Muhammad Sarwar; Muhammad Ashraf Iqbal Mughal (Tropical Animal Health and Production, 2013)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Tissue-specific expression and functional role of dehydrins in heat tolerance of sugarcane (Saccharum officinarum) - Saddia Galani; Abdul Wahid; Muhammad Arshad (Protoplasma, 2013)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

Flow Karyotyping of Wheat Addition Line “T240” with a Haynaldia villosa 6VS Telosome - Dong-wei Guo; Dong-hong Min; Zhao-shi Xu; Ming Chen; Lian-cheng Li; Muhammad Ashraf; Abdul Ghafoor; You-zhi Ma (Plant Molecular Biology Reporter, 2013)

Effects of interactions among Metarhizium anisopliae, Bacillus thuringiensis and chlorantraniliprole on the mortality and pupation of six geographically distinct Helicoverpa armigera field populations - Waqas Wakil; M. Usman Ghazanfar; Tahira Riasat; Mirza Abdul Qayyum; Sohail Ahmed; Muhammad Yasin (Phytoparasitica, 2013)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)

A Parametric Study on Stability of Open Excavations in Alluvial Soils of Lahore District, Pakistan - Muhammad Irfan; Aziz Akbar; Mubashir Aziz; Ammad Hassan Khan (Geotechnical and Geological Engineering, 2013)

A Preliminary Study on the Occurrence and Dissipation of Estrogen in Livestock Wastewater - Xianjin Tang; Naveedullah; Muhammad Zaffar Hashmi; Hu Zhang; Mingrong Qian; Chunna Yu; Chaofeng Shen; Zhihui Qin; Ronglang Huang; Jiani Qiao; Yingxu Chen (Bulletin of Environmental Contamination and Toxicology, 2013)

Comparative study of alleviating effects of GSH, Se and Zn under combined contamination of cadmium and chromium in rice (Oryza sativa) - Fangbin Cao; Nanbo Wang; Mian Zhang; Huaxin Dai; Muhammad Dawood; Guoping Zhang; Feibo Wu (BioMetals, 2013)

Ferrous iron chelating property of low-molecular weight succinoglycans isolated from Sinorhizobium meliloti - Eunae Cho; Jae Min Choi; Hwanhee Kim; Muhammad Nazir Tahir; Youngjin Choi; Seunho Jung (BioMetals, 2013)

Genetic analysis of Newcastle disease virus from Punjab, Pakistan - Muhammad Zubair Shabbir; Muhammad Abbas; Tahir Yaqub; Nadia Mukhtar; Atta Subhani; Hasham Habib; Muhammad Umar Sohail; Muhammad Munir (Virus Genes, 2013)

Decoupling Directed and Passive Motion in Dynamic Systems: Particle Tracking Microrheology of Sputum - Erika J. Fong; Yasha Sharma; Brian Fallica; Dylan B. Tierney; Sarah M. Fortune; Muhammad H. Zaman (Annals of Biomedical Engineering, 2013)

Mitigating Global Warming Potentials of Methane and Nitrous Oxide Gases from Rice Paddies under different irrigation regimes - Muhammad Aslam Ali; M. Anamul Hoque; Pil Joo Kim (Ambio, 2013)

Alleviation of salinity-induced perturbations in ionic and hormonal concentrations in spring wheat through seed preconditioning in synthetic auxins - Muhammad Iqbal; Muhammad Ashraf (Acta Physiologiae Plantarum, 2013)

Nuclear and chloroplast DNA phylogeography reveals P leistocene divergence and subsequent secondary contact of two genetic lineages of the tropical rainforest tree species S horea leprosula ( D ipterocarpaceae) in S outh‐ E ast A sia - Masato Ohtani; Toshiaki Kondo; Naoki Tani; Saneyoshi Ueno; Leong S. Lee; Kevin K. S. Ng; Norwati Muhammad; Reiner Finkeldey; Mohamad Na'iem; Sapto Indrioko; Koichi Kamiya; Ko Harada; et al. (Molecular Ecology, 2013)
Tropical rainforests in S outh‐ E ast A sia have been affected by climatic fluctuations during past glacial eras. To examine how the accompanying changes in land areas and temperature have affected the genetic properties of rainforest trees in the region, we investigated the phylogeographic patterns of a widespread dipterocarp species, Shorea leprosula . Two types of DNA markers were used: expressed sequence tag‐based simple sequence repeats and chloroplast DNA (cp DNA ) sequence variations. Both sets of markers revealed clear genetic differentiation between populations in B orneo and those in the M alay P eninsula and S umatra ( M alay/ S umatra). However, in the south‐western part of B orneo, genetic admixture of the lineages was observed in the two marker types. Coalescent simulation based on cp DNA sequence variation suggested that the two lineages arose 0.28–0.09 million years before present and that following their divergence migration from Malay/Sumatra to Borneo strongly exceeded migration in the opposite direction. We conclude that the genetic structure of S . leprosula was largely formed during the middle P leistocene and was subsequently modified by eastward migration across the subaerially exposed S unda S helf.

Professor Atta-ur-Rahman: towering scientific achievements - Muhammad Iqbal Choudhary (Natural Product Research, 2013)

Friedelin and lanosterol from Garcinia prainiana stimulated glucose uptake and adipocytes differentiation in 3T3-L1 adipocytes - Deny Susanti; Mohamed Zaffar Ali Mohamed Amiroudine; Mohamad Fazlin Rezali; Muhammad Taher (Natural Product Research, 2013)

Antioxidant and lipoxygenase inhibiting new iridoid glucosides from Caryopteris odorata - Tayyaba Shahzadi; Muhammad Athar Abbasi; Aziz Ur-Rehman; Tauheeda Riaz; Khalid Mohammed Khan; Muhammad Ashraf; Iftikhar Afzal; Muhammad Nadeem Akhtar; Muhammad Ajaib (Natural Product Research, 2013)

The nutritional value of peanut hay (Arachis hypogaea L.) as an alternate forage source for sheep - Muhammad Tahir Khan; Nazir Ahmad Khan; Melkamu Bezabih; Muhammad Subhan Qureshi; Altafur Rahman (Tropical Animal Health and Production, 2013)

Thermal stress responses in Antarctic yeast, Glaciozyma antarctica PI12, characterized by real-time quantitative PCR - Sook Yee Boo; Clemente Michael Vui Ling Wong; Kenneth Francis Rodrigues; Nazalan Najimudin; Abdul Munir Abdul Murad; Nor Muhammad Mahadi (Polar Biology, 2013)

Extracting the damaging effects of the 2010 eruption of Merapi volcano in Central Java, Indonesia - Fajar Yulianto; Parwati Sofan; Muhammad Rokhis Khomarudin; Muhammad Haidar (Natural Hazards, 2013)

Synthesis, spectroscopic, and biological evaluation of some levofloxacin metal complexes - Najma Sultana; Muhammad Saeed Arayne; Syeda Bushra Shakeb Rizvi; Urooj Haroon; Muhammad Ahmed Mesaik (Medicinal Chemistry Research, 2013)

Negative Regulation of Methyl Jasmonate-Induced Stomatal Closure by Glutathione in Arabidopsis - Nasima Akter; Eiji Okuma; Muhammad Abdus Sobahan; Misugi Uraji; Shintaro Munemasa; Yoshimasa Nakamura; Izumi C. Mori; Yoshiyuki Murata (Journal of Plant Growth Regulation, 2013)

Detection of Vibrio cholerae and Vibrio vulnificus by duplex PCR specific to the groEL gene - Muhammad Tofazzal Hossain; Yu-Ri Kim; Eun-Young Kim; Jong-Min Lee; In-Soo Kong (Fisheries Science, 2013)

Hydrostratigraphy and hydrogeology of the western part of Maira area, Khyber Pakhtunkhwa, Pakistan: a case study by using electrical resistivity - Asam Farid; Khanzaib Jadoon; Gulraiz Akhter; Muhammad Asim Iqbal (Environmental Monitoring and Assessment, 2013)

Molecular cloning, characterization of CAT, and eco-toxicological effects of dietary zinc oxide on antioxidant enzymes in Eisenia fetida - Wenguang Xiong; Yongxue Sun; Mengjia Zou; Rizwan-Ul-Haq Muhammad (Environmental Science and Pollution Research, 2013)

Isolation and expression analysis of FTZ-F1 encoding gene of black rock fish (Sebastes schlegelii) - Muhammad Shafi; Yanan Wang; Xiaosu Zhou; Liman Ma; Faiz Muhammad; Jie Qi; Quanqi Zhang (Journal of Ocean University of China, 2013)

Photodegradation and Stabilization of Betamethasone-17 Valerate in Aqueous/Organic Solvents and Topical Formulations - Saif-ur-Rehman Khattak; Dilnawaz Shaikh; Iqbal Ahmad; Khan Usmanghani; Muhammad Ali Sheraz; Sofia Ahmed (AAPS PharmSciTech, 2013)

Validation of MODIS, MISR, OMI, and CALIPSO aerosol optical thickness using ground-based sunphotometers in Hong Kong - Man Sing Wong; Muhammad I. Shahzad; Janet E. Nichol; Kwon Ho Lee; P.W. Chan (International Journal of Remote Sensing, 2013)

Synthesis of Amino-Substituted p-tert-Butylcalix[4]arene for the Removal of Chicago Sky Blue and Tropaeolin 000 Azo Dyes from Aqueous Environment - Muhammad Afzal Kamboh; Enise Akoz; Shahabuddin Memon; Mustafa Yilmaz (Water, Air, & Soil Pollution, 2013)

Investigation of equine influenza virus in two geographical regions of Pakistan - Muhammad Sajid; Mansur-ud-Din Ahmad; Muhammad Athar Khan; Muhammad Aftab Anjum; Muhammad Hassan Mushtaq (Tropical Animal Health and Production, 2013)

Identification of differentially expressed genes related to coloration in red/green mutant pear (Pyrus communis L.) - Jun Wu; Guang Zhao; Ya-Nan Yang; Wen-Quan Le; Muhammad Awais Khan; Shao-Ling Zhang; Chao Gu; Wen-Jiang Huang (Tree Genetics & Genomes, 2013)

Anti-inflammatory and selective COX-2 inhibitory activities of metal complexes of Schiff bases derived from aldoses - Mohammad S. Iqbal; Syed J. Khurshid; Bakhtiar Muhammad (Medicinal Chemistry Research, 2013)

Flow injection online spectrophotometric determination of uranium after preconcentration on XAD-4 resin impregnated with nalidixic acid - Shabnam Shahida; Akbar Ali; Muhammad Haleem Khan; Muhammad Mufazzal Saeed (Environmental Monitoring and Assessment, 2013)

Metal pollution and ecological risk assessment in marine sediments of Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2013)

Degradation and Mineralization of Azo Dye Reactive Blue 222 by Sequential Photo-Fenton’s Oxidation Followed by Aerobic Biological Treatment Using White Rot Fungi - Shumaila Kiran; Shaukat Ali; Muhammad Asgher (Bulletin of Environmental Contamination and Toxicology, 2013)

Complete nucleotide sequences of two begomoviruses infecting Madagascar periwinkle (Catharanthus roseus) from Pakistan - Muhammad Ilyas; Kiran Nawaz; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid (Archives of Virology, 2013)

Mineralogy, geochemistry, and reserve estimation of the Euphrates limestone for Portland cement industry at Al-Najaf area, South Iraq - Mautaz Al-Dabbas; Salih Muhammad Awadh; Ayad Abed Zaid (Arabian Journal of Geosciences, 2013)

Influence of Icelandic Low pressure on winter precipitation variability over northern part of Indo-Pak Region - Muhammad Jawed Iqbal; Kashif Ilyas (Arabian Journal of Geosciences, 2013)

LONG‐TERM EFFECTIVENESS OF LINING TERTIARY CANALS IN THE INDUS BASIN OF PAKISTAN - Ali Raza; Muhammad Latif; Abdul Sattar Shakir (Irrigation and Drainage, 2013)
This study was conducted to determine the effectiveness of lining tertiary canals with respect to their lining age. Twenty partially lined canals (1–25 years of lining age) were randomly selected and these were classified into five age groups with a class interval of 5 years. The flow rate of each selected channel was measured at the head and tail of the lined sections, and in the unlined sections at a distance equal to the length of the lined sections. The conveyance losses varied from 0.76 to 1.31 l s ‐1 per 100 m length. The lowest losses were observed in the newly lined canals (1– 5 years old) while the highest losses were observed in the case of group IV, having a lining age of between 16 and 20 years. The conveyance losses were reduced by 47 and 30% respectively in groups I and V. Thus, these results clearly demonstrate that the effectiveness of lining decreases with its age. A significant amount of water is saved by the newly lined canals; however, this benefit decreases as the lining become older. Copyright © 2013 John Wiley & Sons, Ltd.

Application and Opportunities of Pulses in Food System: A Review - Muhammad Asif; Lloyd W. Rooney; Rashida Ali; Mian N. Riaz (Critical Reviews in Food Science and Nutrition, 2013)

Black Pepper and Health Claims: A Comprehensive Treatise - Masood Sadiq Butt; Imran Pasha; Muhammad Tauseef Sultan; Muhammad Atif Randhawa; Farhan Saeed; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2013)

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies - Muhammad Abrar; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Muhammad Atif Randhawa; Farhan Saeed; Khalid Waqas (Critical Reviews in Food Science and Nutrition, 2013)

Nutraceutical and Functional Scenario of Wheat Straw - Imran Pasha; Farhan Saeed; Khalid Waqas; Faqir Muhammad Anjum; Muhammad Umair Arshad (Critical Reviews in Food Science and Nutrition, 2013)

Landslide dam and subsequent dam-break flood estimation using HEC-RAS model in Northern Pakistan - Mohsin Jamil Butt; Muhammad Umar; Raheel Qamar (Natural Hazards, 2013)

Evaluation of synthetic hexaploid wheats (derivative of durum wheats and Aegilops tauschii accessions) for studying genetic diversity using randomly amplified polymorphic DNA (RAPD) markers - Muhammad Shakeel; Muhammad Ilyas; Mujeeb Kazi (Molecular Biology Reports, 2013)

A novel WDR62 mutation causes primary microcephaly in a Pakistani family - Mazhar Mustafa Memon; Syed Irfan Raza; Sulman Basit; Rizwana Kousar; Wasim Ahmad; Muhammad Ansar (Molecular Biology Reports, 2013)

Erratum to: Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammed Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammad Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Evaluation of n-hexane extract of Viola betonicifolia for its neuropharmacological properties - Naveed Muhammad; Muhammad Saeed; Haroon Khan; Ikramul Haq (Journal of Natural Medicines, 2013)

A Validated Spectrofluorimetric Method for the Determination of Citalopram in Bulk and Pharmaceutical Preparations Based on the Measurement of the Silver Nanoparticles-Enhanced Fluorescence of Citalopram/Terbium Complexes - Muhammad Naeem Khan; Jasmin Shah; Muhammad Rasul Jan; Sang Hak Lee (Journal of Fluorescence, 2013)

Penicillium expansum Volatiles Reduce Pine Weevil Attraction to Host Plants - Muhammad Azeem; Gunaratna Kuttuva Rajarao; Henrik Nordenhem; Göran Nordlander; Anna Karin Borg-Karlson (Journal of Chemical Ecology, 2013)

Characterization of Afp1, an antifreeze protein from the psychrophilic yeast Glaciozyma antarctica PI12 - Noor Haza Fazlin Hashim; Izwan Bharudin; Douglas Law Sie Nguong; Sakura Higa; Farah Diba Abu Bakar; Sheila Nathan; Amir Rabu; Hidehisa Kawahara; Rosli Md. Illias; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Extremophiles, 2013)

Sequence determination of a quadripartite dsRNA virus isolated from Aspergillus foetidus - Zisis Kozlakidis; Noemi Herrero; Selin Ozkan; Lakkhana Kanhayuwa; Atif Jamal; Muhammad F. Bhatti; Robert H. A. Coutts (Archives of Virology, 2013)

Genetic diversity in human malarial parasites of Khyber Agency Pakistan - Lubna Khatoon; Muhammad Jan; Inam Khan; Farhat Ullah; Salman Malik (Acta Parasitologica, 2013)
Malaria is wide spread in poor world and its burden has been assessed by the enumeration of malarial parasites in blood of patients. This study was designed to find a relationship between social structure, and spread of malaria in Khyber agency. The average parasite density was 2050 parasite/μl in Khyber Agency. Due to economic and social setup most of the people have habit of sleeping in open air thus playing role in high malaria prevalence and Plasmodium vivax remains the prevalent species. Genetic study performed on 110 Blood samples showed less genetic diversity for both Plasmodium vivax and Plasmodium falciparum. Eight alleles were distinguished both for Pvmsp 3α and Pvmsp 3β in total of 20 and 39 amplified samples of P. vivax respectively. Out of 17 samples amplified for P. falciparum 11 showed genotype K1 and 10 for MAD at Pfmsp-1 while 14 alleles were identified for 3D7/1C and two for FC27 of corresponding families of Pfmsp-2 gene. This shows that Plasmodium parasites are not genetically diverse in Khyber agency.